INVESTIGATION OF THE METHOD OF THERMAL FRICTION TURN-MILLING OF HIGH STRENGTH MATERIALS - Sherov, Karibek; Mussayev, Medgat; Usserbayev, Muratbek; Magavin, Sabit; Abisheva, Nazerke; Karsakova, Nurgul; Kuanov, Issa; Bekzhanov, Yeldos; Myrzakhmet, Balgali (Journal of Applied Engineering Science, 2021)
An analysis of the state of the matter of the manufacture of parts such as bodies of revolution has shown that there is a problem of turning processing by turning large, long parts, connected with increasing productivity and processing quality, as well as reducing the costs of turning operations. To solve this problem, the authors propose a resource-saving combined method for treating external cylindrical surfaces by thermal friction turn-milling.Experimental studies were performed on the processing of the outer cylindrical surface using a special friction cutter made of non-instrumental material. The results showed that with thermal friction turn-milling, it is possible to achieve Ra = 1,0 mcm. The process of chip formation was also investigated and the formation of a retarded layer was established, which protects the surface of the friction cutter from wear.Optimum values of cutting conditions for processing by thermal friction turn-milling of steel 30HGSA.
Keywords: thermal friction turn-milling, roughness, hardness, feed motion, braked layer, high strength material